Refleksi dan Diskusi Kewarganegaraan sebagai Penguatan Kesadaran dan Partisipasi Siswa dalam Pembelajaran Pendidikan Kewarganegaraan - Siti Mei Saroh; Syamzaimar Syamzaimar (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
This study aims to analyze reflection and citizenship discussion as strategies to strengthen democratic awareness and student participation in Civic Education learning. The background of this research is the prevalence of traditional, teacher-centered teaching strategies, which hinder student engagement and understanding of democratic principles. This study combines library research with a qualitative approach. Data on citizenship education, democracy education, reflections, and discussions were collected from various sources, including books, papers, scientific journals, and related documents. The results show that reflection can improve students’ awareness of democratic values, responsibility, tolerance, and the importance of deliberation. Meanwhile, citizenship discussion effectively increases active student participation, argumentation skills, cooperation, and confidence in expressing opinions. The integration of reflection and discussion creates Civic Education learning that is more interactive, critical, and meaningful. The main obstacles include limited learning time, low teacher readiness, and passive student learning culture. Therefore, learning innovation that encourages active student involvement is needed. This study concludes that reflection and citizenship discussion are effective strategies to develop young generations who are democratic, responsible, and participative in national and civic life